Characterization and classification of some intensively cultivated soils from the Ganges river floodplain of Bangladesh - Hossain, MM; Khan, ZH; Hussain, MS; Mazumder, AR (Dhaka University Journal of Biological Sciences, 2011)
Most of the soil samples from four pedons representing some extensive soil series from the Ganges river floodplain of Bangladesh found to be heavy textured with clay content averaging from 43 to 55 per cent up to a depth of one meter. The soils had neutral to alkaline reaction with high percentage of base saturation. Because of seasonal flooding ranging from two - three months the soils have developed redoximorphic features including redox concentration in the middle zone and a redox depletion in the lower zone of the profiles. The seasonal submergence and drying are the most active factors in developing the morphogenetic features in these soils. Smectite was the dominant clay mineral followed by mica and kaolinite with small quantities of vermiculites and interstratified minerals. The minerals in the clay fraction of the soils appear to be inherited from alluvial parent materials with very little in situ mineral transformation. The soils were characterized at the family categoric level of USDA soil taxonomy. Key words: Ganges river floodplain; Characterization; Classification; Cultivated soils DOI: http://dx.doi.org/10.3329/dujbs.v20i1.8870 Dhaka Univ. J. Biol. Sci. 20(1): 71-80, 2011 (January)